Serum vitamin D in obese and overweight subjects according to estimated glomerular filtration rate - Kitsos, Athanasios; Dounousi, Evangelia; Kalaitzidis, Rigas; Challa, Anna; Siamopoulos, Kostas C.; Tigas, Stelios (Hormones (Athens, Greece), 2018)
Objective Obesity and renal disease are both associated with low serum 25(OH)D. The aims of the present study were to (a) assess vitamin D status and compare serum vitamin D levels in overweight/obese versus normal-weight individuals according to eGFR and (b) assess the role of 25(OH)D in the development of secondary hyperparathyroidism (SHPT). Design Serum 25(OH)D, 1,25(OH) 2 D, parathyroid hormone (PTH), calcium, and phosphate were measured in 104 subjects with BMI > 25 kg/m 2 . Participants were categorized according to eGFR (ml/min/1.73m 2 ): G1 ≥ 60 ( n = 53), G2 30–59 ( n = 35), and G3 15–29 ( n = 16). Fifty normal-weight individuals with comparable eGFR served as controls: G1-nw ( n = 23), G2-nw ( n = 18), and G3-nw ( n = 9). Results 25(OH)D levels were lower in G1 compared to those in G1-nw (21.7 ± 6.5 vs 26.5 ± 7.0 ng/ml, p = 0.005), G2 versus G2-nw (19.0 ± 6.0 vs 25.0 ± 5.2 ng/ml, p = 0.001), and G3 vs G3-nw (15.8 ± 4.7 vs 20.3 ± 4.5 ng/ml, p = 0.030). 1,25(OH) 2 D and PTH levels were similar in obese/overweight versus normal-weight individuals in each of the eGFR categories. Factors independently associated with low 25(OH)D levels were BMI > 25 kg/m 2 , lower eGFR, and female gender. Mean 25(OH)D levels were < 30 ng/ml in both overweight and controls, in all eGFR groups. SHPT was universally observed when eGFR was < 30 ml/min/1.73m 2 . Conclusions Lower serum 25(OH)D but similar 1,25(OH) 2 D and PTH levels were observed in overweight/obese compared to normal-weight individuals. Even though vitamin D insufficiency was common across all eGFR categories, secondary hyperparathyroidism was more prevalent as eGFR declined.